Modified RD algorithm of highly squint SAR imaging based on range walk removal. Issue 1 (1st November 2022) - Tang, Chuanbin; Cui, Kaibo; Li, Yueli; Wang, Qingping; Shi, Qingzhan; Yuan, Naichang
Abstract : In highly squint SAR imaging mode, linear range walk (LRW) plays a leading role in range cell migration (RCM), which is much larger than range bending. Based on the geometric model of highly squint SAR imaging, the characteristics of highly squint SAR echoes are analyzed in this paper. And a modified range-Doppler (RD) algorithm is derived, which is suitable for highly squint mode. The algorithm expands the slant distance to the cubic term, correct linear range walk in the time domain, and correct the range bending in the frequency domain. The simulation results of the point targets verify the feasibility of the algorithm. By comparing with the algorithm before the improvement, the effectiveness of the proposed algorithm is proved.